Nutritional and bioactive oils from salmon (Salmo salar) side streams obtained by Soxhlet and optimized microwave-assisted extraction - Fuente, Beatriz de la (2022)
The efficiency of the microwave-assisted extraction (MAE) technique on recovering nutritional and bioactive oils from salmon (Salmo salar) side streams was evaluated and compared to Soxhlet extraction. The response surface methodology (RSM) coupled with a central composite rotatable design was used to optimize time, microwave power, and solid/liquid ratio of the MAE process in terms of oil yield. The optimal MAE conditions were 14.6 min, 291.9 W, 80.1 g/L for backbones, 10.8 min, 50.0 W, 80.0 g/L for heads, and 14.3 min, 960.6 W, 99.5 g/L for viscera, which resulted in a recovery of 69% of the total lipid content for backbones and heads and 92% for viscera. The oils obtained under optimal MAE conditions showed a healthy lipid profile as well as cytotoxic, antioxidant, anti-inflammatory, or antimicrobial properties. These results highlight that oils from underutilized salmon by-products could be exploited by different industrial sectors under the circular economy approach.